Complete Cryptocurrency & Blockchain Course | Learn Solidity - Percival, Rob; Deol, Ravinder; Wiesner, Thomas (Packt Publishing, 2019)
Use Solidity, Remix, Ganache, Geth, Metamask, Truffle, and more to make Blockchain Dapps! Includes cryptocurrency know-how. About This Video Build your own interactive Tic-Tack-Toe game using blockchains Learn how cryptocurrencies and blockchains work In Detail Welcome to one of the largest, most in-depth cryptocurrency and blockchain courses online! This course gives students the chance to work with cryptocurrencies and the blockchain on a practical level, with step-by-step instructions guiding you through the entire process. The first half of this course is a brilliant and insightful introduction to the (often confusing) world of cryptocurrency. You'll learn everything you need to know about: The history and economics of cryptocurrency How to protect yourself and your investment portfolio online. The key differences between hot and cold wallets How to buy, sell, and invest cryptocurrency A dedicated breakdown of various AltCoins (including Litecoin, Ethereum, Ripple, and more!) The hands-on second half of the course teaches students how to build their own projects as an Ethereum blockchain developer! Going step-by-step your instructor, you'll: Tackle hands-on development effectively Build your own interactive Tic-Tack-Toe game using blockchains! Test your skills with practical challenges and exercises! Master core development tools such as Mist, Geth, and Ethereum Studio Learn advanced Web3 development, how to debug your decentralized applications, and loads more! This course is a great intro to the world of cryptocurrencies and the blockchain technology.
Online resource; Title from title screen (viewed September 27, 2019)
Keywords: Cryptocurrencies; Blockchains (Databases); Cryptomonnaie; Chaînes de blocs; cryptocurrencies; Electronic videos